2015
DOI: 10.1186/s12915-015-0221-6
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate enhances skeletal muscle fatty acid oxidation via a nitric oxide-cGMP-PPAR-mediated mechanism

Abstract: BackgroundInsulin sensitivity in skeletal muscle is associated with metabolic flexibility, including a high capacity to increase fatty acid (FA) oxidation in response to increased lipid supply. Lipid overload, however, can result in incomplete FA oxidation and accumulation of potentially harmful intermediates where mitochondrial tricarboxylic acid cycle capacity cannot keep pace with rates of β-oxidation. Enhancement of muscle FA oxidation in combination with mitochondrial biogenesis is therefore emerging as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 56 publications
3
46
2
Order By: Relevance
“…For example, Larsen et al [37] demonstrated that NITR supplementation in healthy, young males led to increased plasma NO concentration and, subsequently, downstream metabolic adaptations, including increased mitochondrial efficiency, reduced proton leak, and ultimately increased ATP production capacity. Similar data have been derived in rats during fatty-acid oxidation [38]. In addition, there is some evidence that NITR supplementation can increase exercise efficiency in humans [3941] and exercise capacity in some disease conditions such as peripheral arterial disease, where NO production is reduced [42].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…For example, Larsen et al [37] demonstrated that NITR supplementation in healthy, young males led to increased plasma NO concentration and, subsequently, downstream metabolic adaptations, including increased mitochondrial efficiency, reduced proton leak, and ultimately increased ATP production capacity. Similar data have been derived in rats during fatty-acid oxidation [38]. In addition, there is some evidence that NITR supplementation can increase exercise efficiency in humans [3941] and exercise capacity in some disease conditions such as peripheral arterial disease, where NO production is reduced [42].…”
Section: Introductionsupporting
confidence: 59%
“…Most pertinently, increasing NO bioavailability through administration of sodium nitrite mitigates functional ischemia in patients with Becker muscular dystrophy [43], suggesting that expansion of the NITR–nitrite–NO pool in DMD may also be beneficial. The results from these studies prompted us to investigate whether increasing NO availability via NITR supplementation, which has been previously proven to increase plasma [37, 44] and skeletal muscle [38] NO levels and elicit beneficial mitochondrial adaptations at the skeletal muscle level [37, 44], would improve mitochondrial function and rectify energy homeostasis dysregulation in dystrophic muscle. Therefore, we investigated whether an established dietary NITR supplementation regimen [44] could improve GU, mitochondrial function, ROS emission, and muscle architecture in healthy (control; CON) and dystrophic ( mdx ) mouse models.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies from our group on rat soleus, we did not see any effect of hypoxia on mass-corrected respiration rates in permeabilised fibres despite some changes in metabolic gene expression, enzyme activities and muscle metabolite concentrations [10,14]. This may highlight a difference in the effect of hypoxia on rats and mice, but may have been due to the shorter duration of hypoxic exposure used previously (2 weeks).…”
Section: Discussionmentioning
confidence: 44%
“…Dietary nitrate supplementation exhibits anti-obesity and anti-diabetic properties in rodents; improving homeostatic model assessment for insulin resistance and quantitative insulin sensitivity check index assessments in high-fructose diet-induced insulin resistant rats (5), and improving glucose tolerance in NOS-deficient mice (4); while reducing adiposity in both models. We have shown that nitrate increases muscle -oxidation and mitochondrial biogenesis (23), and therefore may have utility in treating the intramuscular lipid deposition-induced lipotoxicity and insulin resistance associated with diabetes. However, diabetic myopathy is a major complication of diabetes and is characterized by muscle atrophy and reduced physical performance and muscle capacity (20).…”
Section: Discussionmentioning
confidence: 99%
“…During the 6 day differentiation, cells were cultured with either saline (control), 25 M NaNO3, or 500 M NaNO3 or, during the sodium nitrite studies (NaNO2), with saline (control), 500 nM NaNO2, β5 M NaNO2 or 500 M NaNO2 (Ultra-pure, Sigma-Aldrich). Differentiation of C2C12 cells is unaffected by NaNO3 (23). Pharmacological agent studies utilized 2,2-Bipyridyl (100 µM), 2-Phenyl- [4,3-a]quinoxalin-1-one (ODQ) (1 M), GW74β (100 nM) and sildenafil (1 µM) (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%